Molecular monitoring of response to imatinib (Glivec®) in CML patients pretreated with interferon alpha. Low levels of residual disease are associated with continuous remission - Paschka, Peter; Müller, Martin Christian; Merx, Kirsten; Kreil, Sebastian; Schoch, C.; Lahaye, T.; Weißer, Andreas; Petzold, A.; König, H.; Berger, Ute; Gschaidmeier, Harald; Hehlmann, Rüdiger; et al. (Leukemia, 2003)
A significant proportion of chronic myeloid leukemia (CML) patients achieve a major cytogenetic remission (MCR) to imatinib therapy after failing interferon (IFN) α-based protocols. We sought to determine levels of residual disease in patients with MCR using various molecular methods and to establish a relation between residual BCR-ABL transcript levels and rate of relapse in complete cytogenetic remission (CCR). Response was measured by conventional cytogenetic analysis, hypermetaphase and interphase fluorescence in situ hybridization (HM-FISH, IP-FISH) of bone marrow (BM) cells, qualitative nested and quantitative reverse transcriptase polymerase chain reaction (RT-PCR) for BCR-ABL transcripts. We investigated 323 peripheral blood (PB) and BM samples from 48 CML patients who achieved a complete (Ph+ 0%; n=41) or partial (Ph+ 1-34%; n=7) cytogenetic remission after 3-20 months of imatinib therapy. Prior to imatinib, 35 patients were in chronic phase (CP), eight in accelerated phase (AP), four in myeloid and one in lymphoid blast crisis. HM-FISH results correlated with ratios BCR-ABL/ABL in PB and BM. In patients with CCR, residual disease was detectable by HM-FISH (31%), IP-FISH (18%), and RT-PCR (100%). During follow-up, BCR-ABL became undetectable in two patients (one CP, one AP) by both nested and quantitative RT-PCR. CCR is ongoing in 30 evaluable patients, 11 patients have relapsed. At the time of best response, median ratios BCR-ABL/ABL were 2.1% (range 0.82-7.8) in patients with subsequent relapse and 0.075% (range 0-3.9) in patients with ongoing remission (P=0.0011). All 16 CP patients, who achieved ratios BCR-ABL/ABL <0.1% as best molecular response are in continuous remission, while 6/13 patients (46%) with ratios ⩾0.1% have relapsed (P=0.0036). We conclude that: (i) in patients with CCR to imatinib, HM-FISH and RT-PCR usually reveal residual BCR-ABL+ cells; (ii) RT-PCR results derived from PB and BM are comparable in CP CML; and (iii) low levels of residual disease with ratios BCR-ABL/ABL <0.1% are associated with continuous remission.
Gesehen am 16.05.2022